Burnout, work engagement and life satisfaction among Spanish teachers: The unique contribution of core self-evaluations. (October 2022) - Peláez-Fernández, María Angeles; Mérida-López, Sergio; Rey, Lourdes; Extremera, Natalio
Abstract: The aim of this study was to examine burnout and engagement dimensions as predictors of life satisfaction in a sample of 531 Spanish teachers. We also aimed to examine the additional contribution of core self-evaluations on life satisfaction, above and beyond socio-demographic variables and burnout and engagement dimensions. Results of hierarchical regression analyses indicated that core self-evaluations explained a substantial and unique amount of variance in life satisfaction beyond and above that accounted for age, one burnout dimension (i.e., personal accomplishment) and one engagement dimension (i.e., dedication). Additional analysis found that personal accomplishment and dedication mediated the link between core self-evaluations and life satisfaction. Some practical implications of the current findings for educational context are discussed. Highlights: We tested CSE as a predictor of teachers' life satisfaction above burnout and engagement. Personal accomplishment and dedication emerged as predictors of life satisfaction. Personal accomplishment and dedication mediated the link CSE-life satisfaction. CSE predicted life satisfaction beyond and above burnout and engagement. Strengths-based interventions are key to increase teachers' well-being.